Implementation of CHSE based on Health Protocol (Cleanliness, Healthy, Safety and Environment Sustainability) in Desa Wisata Silalahi II, Dairi Regency - Hetty Claudia Nainggolan (Tourism, Hospitality And Culture Insights Journal, 2021)
Decree of Kepala Badan Nasional Penanggulangan Bencana Nomor 9A Tahun 2020 concerning the determination of the status of a certain emergency situation for the disease outbreak due to Covid-19 in Indonesia, it has had a major impact on various sectors, especially the tourism sector. In an effort to restore the national economy, especially in the tourism sector, the government through Kementrian Pariwisata dan Ekonomi Kreatif has intensified the CHSE program. Where CHSE is the Application of Health Protokol Based on Cleanliness, Health, Safety, and Environment Sustainability. It is hoped that all businesses in the tourism sector can implement this program. The importance of implementing a CHSE-based health protokol is aimed at all parties, from manager’s/business owners, employees, tour guides, guests/visitors/tourists, community groups, associations to local governments. Desa Wisata Silalahi II is one of the tourism villages that is developing by adding facilities, facilities and infrastructure and strengthening human resources in various tourism fields which have also experienced the impact of Covid-19. Using qualitative research methods, using observation data collection techniques, and using checklists and direct interviews with respondents according to research needs, with descriptive analysis techniques, the results of the study found tourist attractions in Desa Wisata Silalahi II had implemented health protokols, however, there were still attractions tourism facilities that have minimal facilities/facilities in accordance with CHSE-based health protokol standards, so it is hoped that there will be collaboration and cooperation between local governments and management of tourist attraction managers, associations, POKDARWIS, local tour guides to add these facilities/facilities and commitment is needed in carrying out CHSE-based health protokol sustain.